Impact of ivermectin and vector control on onchocerciasis transmission in Togo: Assessing the empirical evidence on trends in infection and entomological indicators - Vinkeles Melchers, Natalie V. S.; Agoro, Sibabi; Togbey, Kwamy; Padjoudoum, Koffi; Telou, Ibrahim Gado; Karabou, Potchoziou; Djatho, Touka; Datagni, Michel; Dorkenoo, Ameyo Monique; Kassankogno, Yao; Bronzan, Rachel; Stolk, Wilma A. (PLOS Neglected Tropical Diseases, 2024)
Background The World Health Organization’s 2021–2030 Road Map for Neglected Tropical Diseases boosted global commitment towards the elimination of onchocerciasis, but the timeline to elimination will vary strongly between countries in Africa. To assess progress towards elimination in the Republic of Togo, we reviewed the history of control and time trends in infection. Methodology/principal findings We collated all available programmatic, entomological, and epidemiological data since the initiation of the Onchocerciasis Control Programme (OCP) in Togo through different data sources. We then visualised data trends over time, to assess the impact of interventions on infection and transmission levels. Vector control was initiated by OCP from 1977 (northern and central parts of Togo) or 1988 (southern regions) up to 2002 (most areas) or 2007 (“special intervention zones” [SIZ], parts of Northern and Central Togo). Between 1988 and 1991, Togo initiated ivermectin mass drug administration (MDA) in eligible communities. The impact of vector control was high in most river basins, resulting in low annual biting rates and annual transmission potential declining to very low levels; the impact was lower in river basins designated as SIZ. Repeated, longitudinal ivermectin mass treatments have overall strongly reduced onchocerciasis transmission in Togo. Epidemiological surveys performed between 2014 and 2017 showed that the prevalence of skin microfilariae (mf) and anti-OV16 IgG4 antibodies had declined to low levels in several districts of the Centrale, Plateaux, and Maritime region. Yet, relatively high mf prevalences (between 5.0% and 32.7%) were still found in other districts during the same period, particularly along the Kéran, Mô and Ôti river basins (SIZ areas). Conclusions/significance Trends in infection prevalence and intensity show that onchocerciasis levels have dropped greatly over time in most areas. This demonstrates the large impact of long-term and wide-scale interventions, and suggest that several districts of Togo are approaching elimination.